Responding to Brillantes An Evaluation of Student Responses to 'Faith, Love, Time, and Dr. Lazaro' - Narciso, Alana Leilani C.; Partosa, Lady Flor N. (Silliman Journal, 2022)
This paper draws on reader-response theories to bridge the gap between the reader and the text, a serious concern in literature classrooms. Taking a look at this connection, the study evaluates reflection papers written by students from four different Philippine literature classes on Gregorio Brillantes’ short story “Faith, Love, Time, and Dr. Lazaro.” It peruses the effects of the interaction of reader and text— how the reader interprets the text, to what extent does s/he use the cues in the text, how does s/he relate her personal experience to get meaning out of the text, and in the process of reading, what have the reader realized. It is the hope of this paper to prove that reflective reading—an intellectual as well as personal experience for students— anchored in the text, will help them create meaning of literature and the reading experience and reate such meaning to their lived experiences.